Pembuatan Media Pembelajaran Motor Starter Konvensional bagi Mahasiswa Program Studi D3 Pemeliharan Mesin Otomotif Politeknik Cristo Re - Romualdus Paulus Sogen; Natalia Kristiani Tandafatu (Jurnal Projemen UNIPA, 2025)
The issue addressed in this research is the lack of learning media that support the Electric Vehicle Systems course in the D3 Automotive Engine Maintenance Study Program at Cristo Re Polytechnic. The objectives of this research are to design a conventional starter motor learning media that is easy to understand and functions properly; to create the conventional starter motor learning media; and to test the conventional starter motor learning media. This research was conducted at Cristo Re Polytechnic, in the D3 Automotive Engine Maintenance Study Program. The conventional starter motor learning media was developed through several stages: design, construction, and testing. The design process involved determining the frame to be used, the mounting for the starter motor on the frame, and identifying the panel to be used in the learning media. The construction process included cutting the parts to be used for the frame and the motor mount, assembling or forming the frame, and painting. After the learning media was completed, it underwent testing, which consisted of functional tests such as component testing, system testing, voltage drop testing, and feasibility testing through a questionnaire. The conclusions from the testing results are as follows: the starter motor can operate properly. This is based on the construction of the learning media being in accordance with the design, including the frame dimensions and the printed layout matching the design. In addition, the component testing—which included the ignition switch, relay, and solenoid—showed results that matched the specifications of each component. The system function test showed that the system can operate with or without a relay. The voltage drop test yielded results of 0.2 V for the positive battery voltage drop, 0.1 V for the negative battery voltage drop, and 1 V for the voltage drop in the circuit, all of which are within the specified range. The feasibility test involved distributing a questionnaire to lecturers and several students to evaluate the result of the media development, and from this test, an average score of 3.87 was obtained, categorized as very good.